Casa a Lottano, Il Suono - Emanuele Scaramellini (ArchAlp)
The process that led to the design of Casa a Lottano is investigated from an unseen point of view. Drawing on Valerio Olgiati’s request to his most illustrious colleagues to point out the images that materialised in their minds before beginning the design process, this article explores this journey from the point of view of sound. Architecture is explained and deconstructed through sound: melodic, ordered compositions; and noises, necessary and material. Essential for the author is in fact the aural stimuli that a place arouses when one observes it, studies it. There are sonorities that inexorably accompany the perception of a space, be it the noises caused by the creaking of doors or individual musical compositions sung or listened to that create a kind of soundtrack. At Casa a Lottano, melodies are suggested by the structure’s relationship with nature, by the beautiful scenery of the Alpine setting, open in front of the large glazing, evoking a connection with the sound of the Universe, as interpreted by Pink Floyd. Antithetically, the interior spaces, clean and essential, at times severe in their composition, are realised with clear lines, creating tensions that are as haunting as the notes of a cello. At the same time, the sounds of the materials themselves are investigated, the sensations they cause examined through a mixture of memories and research. Ultimately, it is unclear how exactly this acoustic phenomena develops: do the sounds evoked by a building that has not been built exist in themselves, or are they the result of our experiences?